S2k guidelines for the treatment of psoriasis in children and adolescents – Short version part 2. (20th September 2019) - Eisert, Lisa; Augustin, Matthias; Bach, Sabine; Dittmann, Martin; Eiler, Renate; Fölster‐Holst, Regina; Gerdes, Sascha; Hamm, Henning; Höger, Peter; Horneff, Gerd; von Kiedrowski, Ralph; Philipp, Sandra; et al.
Summary: The present guidelines are aimed at residents and board‐certified physicians in the fields of dermatology, pediatrics, pediatric dermatology and pediatric rheumatology as well as policymakers and insurance funds. They were developed by dermatologists and pediatric dermatologists in collaboration with pediatric rheumatologists using a formal consensus process (S2k). The guidelines highlight topics such as disease severity, quality of life, treatment goals as well as problems associated with off‐label drug therapy in children. Trigger factors and diagnostic aspects are discussed. The primary focus is on the various topical, systemic and UV‐based treatment options available and includes recommendations for use and treatment algorithms. Other aspects addressed herein include vaccinations in children and adolescents with psoriasis as well as various disease subtypes such as guttate psoriasis, diaper psoriasis, pustular psoriasis and psoriatic arthritis. Finally, we also provide recommendations for imaging studies and the diagnostic workup to rule out tuberculosis prior to initiating systemic treatment. Note : This article constitutes part 2 of the Sk2 guidelines for the treatment of psoriasis in children and adolescents. Part 1 was published in last month's issue. It contained introductory remarks and addressed aspects of diagnosis and topical treatment.